Relevance of epithelial-to-pericyte transition in cancer. (2nd January 2017) - Shenoy, Anitha K.; Lu, Jianrong
ABSTRACT: The relevance of epithelial-to-mesenchymal transition (EMT) in cancer is still under debate. Recently, we reported that EMT bestows key pericyte properties on cancer cells and may thus represent epithelial-to-pericyte transition (EPT). Carcinoma cells undergo EPT to stabilize blood vessels and fuel primary tumor growth. Association of EPT cancer cells with vascular niches may also promote resistance to therapy.